Acute endomyocardial disease in infants and children : the relationship between acute myocarditis and endocardial fibroelastosis - Joffe, Hymie Simon (Department of Paediatrics and Child Health, 2018)
This prospective study of acute myocarditis (AM) and endocardial fibroelastosis (EFE) was prompted by their common occurrence in infants and children in Cape Town, and by the persisting controversy regarding the possible relationship of these two conditions to each other, and to idiopathic, chronic, congestive cardiomyopathy (COCM). Patients with AM and EFE were analysed concurrently and over the long-term. The following hypotheses were investigated: A) that AM and EFE represent different phases of a common disease process, and B) that either AM or EFE evolves into COCM. From 1st June 1970 to 31st December 1976 (a study period of 6 years 7 months), 140 consecutive patients with AM or EFE were evaluated, and continually observed until 31st March 1979 (a total observation period of 8 years 10 months). Because there is no definitive, non-invasive, in-vivo diagnostic test for AM or EFE, an inclusive diagnosis of acute endomyocardial disease (EMD) was made in 123 patients who fulfilled all 4 rigid clinical criteria, i.e. a short history ( < 1 month), clinical evidence of myocardial involvement (heart failure, gallop rhythm or shock), radiological cardiomegaly (CTR > 0.55), and ST/T wave changes on electrocardiogram (ECG). Acute EMD was confirmed in all 20 patients who came to autopsy. A further 17 patients with insufficient clinical data had EMD at post-mortem.